Accelerating student and staff learning : purposeful curriculum collaboration - Psencik, Kay. 4 0 16; 5 (Thousand Oaks, CA : Corwin, 2009)
Provides guidance for educators to collaborate with their colleagues on the creation of curriculum that ties into educational standards then implement and monitor the effectiveness of their instruction.
An overview : collaborative curriculum design as professional learning -- Establishing assumptions about student and staff learning -- Determining complex curriculum standards and concepts -- Mapping the curriculum -- Assessment of student learning -- Designing instruction -- Analyzing student work and monitoring student learning to inform instruction -- Using effective grading and parent reporting practices -- Leading schools to sustain the effort and fulfill the promise.
Includes bibliographical references (page 161-165) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Learning.;Curriculum planning.;Group work in education.;Education.;Curriculum planning.;Cooperative learning; 20; 2